1977
DOI: 10.1136/bmj.1.6072.1321-a
|View full text |Cite
|
Sign up to set email alerts
|

Detecting wakefulness during general anaesthesia for caesarean section.

Abstract: Pseudomembranous colitis and co-trimoxazolePseudomembranous colitis is associated with antibiotic treatment. We report here its first published link with co-trimoxazole. Case reportAn 80-year-old woman was admitted to hospital with a fractured neck of the femur, which was managed by internal fixation. Antibiotic cover was not provided for the operation. On the sixth day after operation she developed a fever, which was clinically attributed to a urinary infection, although no organism was subsequently cultured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(71 citation statements)
references
References 3 publications
3
63
0
5
Order By: Relevance
“…Another intraoperative awareness phase is the state of wakefulness, when the patient is able to react to stimuli during surgery, but does not recall nor is conscious of the experienced reactions 5 .…”
Section: General Anesthesia and Intraoperative Awarenessmentioning
confidence: 99%
“…Another intraoperative awareness phase is the state of wakefulness, when the patient is able to react to stimuli during surgery, but does not recall nor is conscious of the experienced reactions 5 .…”
Section: General Anesthesia and Intraoperative Awarenessmentioning
confidence: 99%
“…Unfortunately, the technique is limited by the time that the tourniquet can remain inflated and also the surgeon and surgical field may be disturbed by any sudden unexpected movement of the isolated arm. Tunstall used the technique during anaesthesia for Caesarean section and nine of his 12 patients showed marked arm movements during the procedure, four of the nine responding appropriately to instructions [27]. Russell has demonstrated that 61% of a group of patients anaesthetised with thiopentone, tubocurarine and nitrous oxide/oxygen (70:30), with modest hyperventilation, were able to move their arm to command, were free of pain but had no explicit recall of intra-operative events.…”
Section: Conscious Perception Without Explicit Memorymentioning
confidence: 99%
“…They actually range from 30 to 100 Hz and may overlap with the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). It is believed that an important function of the '40-Hz' rhythm is to bind together the many discontinuous cortical networks needed in the conscious process.…”
Section: The 40-hz Steady-state Responsementioning
confidence: 99%
“…[2][3][4] Although the brain is the major target organ of anaesthetic drugs, ironically this organ system has been largely ignored in routine monitoring during anaesthesia and major surgery. The complexity of the equipment and the difficulty of reading an unprocessed EEG tracing has limited its use in the operating room.…”
Section: En Utilisant Sur L'avant-bras La Technique De Tunstall Du Gamentioning
confidence: 99%